First characterization of seasonal variations in biomarkers baseline in Patella sp. from Mediterranean ports (North Corsica, France). (February 2023) - Pillet, Marion; Muttin, Frédéric; Marengo, Michel; Fullgrabe, Lovina; Huet, Valérie; Lejeune, Pierre; Thomas, Hélène
Abstract: In port areas the identification of contamination sources is necessary for an efficient management. Biomonitoring provides information on the environmental impact of the pollutants. It is often difficult to differentiate the natural variations of biomarkers from those induced by pollution. The present study aims to define a baseline level for biochemical biomarkers in limpet ( Patella sp.) collected in four North-Corsica port areas. Reference data for five biomarkers (superoxide dismutase, glutathione S-transferase, laccase, pyruvate kinase and acetylcholinesterase) were described in a model, using length of the limpet shell, temperature and salinity. The measured biomarkers responses on potentially polluted sites usually fell within the range of the expected values for an unaffected site, suggesting that a main part of the variations is explained by environmental conditions. Not included in the model, biological factors (sex, development stage, etc.), annual variation or other physico-chemical parameter could explain the variations in the model. Highlights: Limpet as bioindicator of environmental quality in port area Baseline levels of five biomarkers of effects Multiple polynomial regression model to integrate confounding factors Considering spatial and temporal environmental variations in biomarker responses